2008
DOI: 10.1097/tp.0b013e318170b6bb
|View full text |Cite
|
Sign up to set email alerts
|

Donor Postextubation Hypotension and Age Correlate With Outcome After Donation After Cardiac Death Transplantation

Abstract: Time between profound instability and cold perfusion is a better predictor of outcome than time from extubation to asystole. If validated, this information could be used to predict DGF after DCD renal transplant and improve outcomes after DCD liver transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 26 publications
2
72
1
Order By: Relevance
“…Using the time from withdrawal to perfusion as a surrogate for warm ischaemic damage may therefore be inadvisable. Recent analyses of kidneys transplanted from DCD donors did not show a statistically significant association between agonalphase characteristics and long-term graft function 12,27 . In contrast, DCD livers appeared more sensitive to ischaemic injury, and a systolic blood pressure of less than 50 mmHg for more than 15 min was associated with poorer graft outcome 27 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Using the time from withdrawal to perfusion as a surrogate for warm ischaemic damage may therefore be inadvisable. Recent analyses of kidneys transplanted from DCD donors did not show a statistically significant association between agonalphase characteristics and long-term graft function 12,27 . In contrast, DCD livers appeared more sensitive to ischaemic injury, and a systolic blood pressure of less than 50 mmHg for more than 15 min was associated with poorer graft outcome 27 .…”
Section: Discussionmentioning
confidence: 96%
“…Recent analyses of kidneys transplanted from DCD donors did not show a statistically significant association between agonalphase characteristics and long-term graft function 12,27 . In contrast, DCD livers appeared more sensitive to ischaemic injury, and a systolic blood pressure of less than 50 mmHg for more than 15 min was associated with poorer graft outcome 27 . The tolerance of the pancreas to warm ischaemia is likely to be between these extremes, as animal models have shown decreased islet viability after warm ischaemia of more than 30 min 28 -30 .…”
Section: Discussionmentioning
confidence: 96%
“…Consensus statements recommend that organ procurement be abandoned 1 hour after withdrawal of life-sustaining therapy, but there is evidence that duration of DWI does not correlate with recipient outcome in DCD kidney transplantation (9,10). Ho et al identified a trend toward an association between prolonged postextubation hypotension and DGF, but this result failed to achieve statistical significance (11). In addition to measuring the impact of DWI duration, Reid et al assessed multiple features of the agonal phase in cardiac death including prolonged hypotension, lactic acidemia, and hypoxia, but none were significant predictors of adverse outcomes (9).…”
Section: Introductionmentioning
confidence: 85%
“…The drive for a shorter agonal period has come mainly from liver transplantation. However, Ho et al [85] demonstrated that postextubation parameters, including duration and severity of hemodynamic instability or hypoxia might be a better predictor of subsequent graft function than just the agonal period.…”
Section: Agonal Phasementioning
confidence: 99%